Nature Integrated Architectural Design: Construction of a Habitable Tree House in Khon Kaen - Reichel, Rainer C.; Boonyaputthipong, Chumnan (International Journal of Building, Urban, Interior and Landscape Technology, 2021)
Worldwide biodiversity is in severe and accelerating decline, often due to land use changes, resulting in a loss of ecosystem services. Northeast Thailand, including Khon Kaen, has seen a reduction in forest cover from 90% to 14% in the last century. New types of sustainable, nature integrated architecture is needed in remaining patches of forest; this will simultaneously preserve biodiversity, sustain ecosystem services, create economic value, and enable nature-based lifestyles and experiences for humans. This paper describes the construction process of a habitable, nature integrated tree house on a 0.5 hectare plot of native forest, in Khon Kaen, Thailand, using locally available materials. The tree house, with 62 m2 of living space is supported exclusively by mature native trees, using locally manufactured tree house attachment bolts (TABs). Functions of the resulting space include sleeping, working, bathing, cooking, eating, and guest visits. The results of the construction are proof that habitable, tree supported dwellings are feasible in Khon Kaen, Thailand.